The Accuracy of Profit Forecasts of the Malaysian KLSE Second Board Initial Public Offers - Cheng, Sim Meng (1997)
This research project attempts to examine the accuracy of the profit forecasts reported in the prospectus of the initial public offers companies who have seek listing on the Kuala Lumpur Stock Exchange Second Board. Speculation that there is a tendency of management to either over forecast or under forecast will also be examined. The study will also relate the forecast errors as a function of a few variables, namely, specific characteristics, Auditors and choice of the Merchant Banker used for the listing. It wiD envisage to obtain some explanation as to the accuracy of the profit forecast and also with it's determinant factors. Secondary data were collected from the KLSE library and the period under review is from it's inception till end of 1996. Accuracy is measured by forecast errors, absolute forecast errors and it's squares forecast errors. In addition, the forecast error obtained was used to test six hypothesis. These hypothesis would help to establish whether there were any relationship between the accuracy in profit forecast and the firm's specific characteristics. The mathematical model used here were the mUltiple regression, ANOVA and R-squared. Results of this study showed that the level of forecast accuracy in an emerging market like Malaysia appeared to be very much better than that reported by studies in the developed markets. Many companies have showed compliance with the 10% deviation ruling by the Securities Commission. The tendency for management to either over forecast or under forecast is not present. This could be attributable to the management obligation to meet it's profits forecast for the three yean, which they have indicated to the Securities Commission The study concluded with establishing that there is no statistically significant differences between accuracy in forecast and the firm's specific characteristics.